Designing a Pure Sine Wave Inverter 250 VA Based on EGS003 - Pashadewa, Alannafi Husein Bayu; Aji, Wahyu Sapto (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
The design of a pure sine wave inverter based on the EGS003 aims to improve the efficiency of electrical energy conversion. This inverter development method integrates PWM (Pulse Width Modulation) control with a pure sine wave reference signal. The use of PWM control allows precise adjustment of the pulse width of the output signal, according to the desired sine wave characteristics. Consequently, this inverter is capable of producing pure sine waves without significant harmonic distortion, enhancing the quality of the generated power and reducing energy losses due to harmonic distortion. This research involves the implementation of EGS003 technology, which is a dedicated PWM controller designed for inverter applications. The use of this controller enables the optimization of resource utilization and enhances energy conversion efficiency. Furthermore, the development of the EGS003-based inverter involves the analysis and design of control circuits in line with modern power electronics principles. This includes adjusting PWM control parameters to various load characteristics, allowing the inverter to operate optimally under different usage conditions. The design results demonstrate that the pure sine wave inverter based on EGS003 provides satisfactory performance in delivering output compliant with power quality standards. With the capability to generate pure sine waves without significant harmonic distortion, this inverter has broad application potential in power systems requiring high-quality power. Additionally, the use of PWM control technology in this inverter facilitates ease of operation adjustment and monitoring, enhancing the overall reliability and efficiency of the system.